Impaired learning and memory generated by hyperthyroidism is rescued by restoration of AMPA and NMDA receptors function - Wei Zhu; Fengming Wu; Jiong Li; Lianghui Meng; Wenjun Zhang; Huijie Zhang; Shuhan Cha; Jifeng Zhang; Guoqing Guo (Neurobiology of Disease, 2022)
Hyperthyroidism has been identified as a risk factor for cognitive disorders. The hippocampus is a key brain region associated with cognitive function, among which excitatory synapse transmission plays an important role in the process of learning and memory. However, the mechanism by which hyperthyroidism leads to cognitive dysfunction through a synaptic mechanism remains unknown. We investigated the synaptic mechanisms in the effects of hyperthyroidism in an animal model that involved repeated injection of triiodothyronine (T3). These mice displayed impaired learning and memory in the Novel object recognition test, Y-maze test, and Morris Water Maze test, as well as elevated anxiety in the elevated plus maze. Mature dendritic spines in the hippocampal CA1 region of hyperthyroid mice were significantly decreased, accompanied by decreased level of AMPA- and NMDA-type glutamate receptors in the hippocampus. In primary cultured hippocampal neurons, levels of AMPA- and NMDA-type glutamate receptors also decreased and whole-cell patch-clamp recording revealed that excitatory synaptic function was obviously attenuated after T3 treatment. Notably, pharmacological activation of AMPAR or NMDAR by intraperitoneal injection of CX546, an AMPAR agonist, or NMDA, an NMDAR agonist can restore excitatory synaptic function and corrected impaired learning and memory deficit in hyperthyroid mice. Together, our findings uncovered a previously unrecognized AMPAR and NMDAR-dependent mechanism involved in regulating hippocampal excitatory synaptic transmission and learning and memory disorders in hyperthyroidism.